Implementation of Cali's food system profile as a pedagogical tool for environmental awareness raising - Rankin S; Perez, J.M. (2021)
Education in schools can be a key driver for the rescue of the planet and its sustainability, without sacrificing progress. Education that teaches students to understand their active role in these processes, a sustainable use of natural resources, healthy food habits and critical and responsible consumption.